Employee assistance programs in Australia: the perspectives of organisational leaders across sectors. (15th September 2016) - Joseph, Beulah; Walker, Arlene
Abstract : Employee assistance programs (EAPs) are employee services that assist in managing a range of issues. This paper posits that in order to ascertain the effectiveness of EAPs, it is critical to identify their purpose and how EAPs are embedded and utilised in organisations to inform evaluations of the programs. A qualitative study investigating how and why EAPs are used in organisations was undertaken. Participants were organisational leaders (3 males, 13 females) representing major industries in Australia. Semi‐structured interviews were used to collect data and thematic analysis delineated two categories and eight themes. These highlighted that participants primarily used external program providers and considered EAPs to be a vital resource of support for staff, a cost‐effective mechanism for managing risk and developing staff, and industry expectation. Participants differed on their perspectives of how to position EAPs in organisations and what should be offered as core services of EAPs. Key points: Participants primarily used external program providers due to the confidentiality afforded by this model. Employee assistance programs are a vital staff support, cost effective in managing risk and an industry expectation. Participants differed on how to position EAPs in organisations and what the core EAP services are.